Preparation, intercalation, and characterization of nanostructured (Zn, Al) layered double hydroxides (LDHs). (1st June 2018) - Richetta, M.; Varone, A.; Mattoccia, A.; Medaglia, P.G.; Kaciulis, S.; Mezzi, A.; Soltani, P.; Pizzoferrato, R.
Abstract : The term layered double hydroxides (LDHs) is used to define synthetic or natural lamellar hydroxides with 2 or more kinds of metallic cations in the main layers, and hydrated interlayer domains, containing anionic species. Layered double hydroxides, also known as hydrotalcite materials, have attracted considerable interest from both industry and academia. They are interesting for their intercalation properties as they are capable of accommodating complex organic molecules. Therefore, they find applications in various fields such as separation technology, catalysis biomedical science, and nanocomposite material engineering. First of all 4, in the context of this work, we present 4 samples of (Zn, Al) LDHs, representative of the 2 hosted anions (Cl − and NO3 − ), prepared with a simple single‐phase hydrothermal technique, using Zn salt as a precursor, deposited on sheets of Al, active as reagent and as a substrate. These preliminary samples, grown for 6 and 24 hours, were intercalated with spermidine and putrescine. Later, (Zn, Al) LDH powders obtained by coprecipitation and intercalated with amino acid cysteine were studied. The properties of LDH nanoplatelets were analysed by surface‐sensitive techniques. X‐ray photoelectron spectroscopy, energy dispersive X‐ray spectroscopy, and possibly ultraviolet photoelectron spectroscopy (spectroscopy techniques) have been exploited to investigate the composition of the samples. The structure of LDHs was inspected by X‐ray diffraction, whereas the morphology was investigated by scanning electron microscopy.